2019
DOI: 10.1016/j.heliyon.2018.e01005
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of core-shell nanocomposites Au catalysts towards abatement of environmental pollutant Rhodamine B

Abstract: Magnetically recoverable Au nanoparticles immobilized/stabilized on core-shell nanocomposites are synthesized by the combination of suspension polymerization as well as surface initiator atom transfer radical polymerization (SI-ATRP) methods. The magnetic core-shell supported Au nanocatalysts are namely Fe3O4-PAC-AuNPs, Fe3O4-PVBC-g-PAC-AuNPs, Fe3O4-HEA-AuNPs, and Fe3O4-PVBC-g-HEA-AuNPs. Among all the catalysts, Fe3O4-PVBC-g-PAC-Au NPs exhibited an excellent activity in the reduction of Rhodamine B with an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 42 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…Many research papers in which AuNPs have shown promising antimicrobial activities have highlighted a majority spherical shape character of the NPs. Nevertheless, rod-shaped, triangular, hexagonal, and cubic NPs have also been found as part of the obtained mixture [ 133 ]. Thangamani et al synthesized AuNPs using Simarouba glauca leaf extract.…”
Section: Aunps and Agnps Applications In Agriculturementioning
confidence: 99%
“…Many research papers in which AuNPs have shown promising antimicrobial activities have highlighted a majority spherical shape character of the NPs. Nevertheless, rod-shaped, triangular, hexagonal, and cubic NPs have also been found as part of the obtained mixture [ 133 ]. Thangamani et al synthesized AuNPs using Simarouba glauca leaf extract.…”
Section: Aunps and Agnps Applications In Agriculturementioning
confidence: 99%
“…The core shell hybrid catalysts have various applications such as conversion of carbon dioxide photo catalytically and hydrocarbon reforming [125–131] . The core shell technology combines the features of core and shell materials to facilitate a two‐stage process in one phase [132,133] .…”
Section: State Of Art Updates On the Conversion Of Syngas To Lpgmentioning
confidence: 99%
“…The core shell hybrid catalysts have various applications such as conversion of carbon dioxide photo catalytically and hydrocarbon reforming. [125][126][127][128][129][130][131] The core shell technology combines the features of core and shell materials to facilitate a two-stage process in one phase. [132,133] Several studies had been performed to synthesis a core shell hybrid catalyst through the direct technique, which are summarized in Table 5.…”
Section: Recent Studies On the Synthesis Of Core Shell Catalystsmentioning
confidence: 99%
“…Development of sustainable and cost-effective catalysts is crucial for fundamental investigation and producing fine chemicals, fuel, polymers, and pharmaceutical ingredients. In this context, Co-, [1] Ni-, [2] Rh-, [3,4] Ir-, [5] Pd-, [6] Pt-, [7] Ru-, [8] and Au [9][10] -based homogeneous catalysts are used to hydrogenate alkenes, N-heteroarenes, ketones, and nitroaromatics with optimum efficiency. For example, Jia and co-workers reported a Rh-based chiral diphenylphosphine ligand for the asymmetric hydrogenation of functionalized olefins.…”
Section: Introductionmentioning
confidence: 99%